Trends in Writing Assessment Research in Indonesia: A Bibliometric Study - Hoinbala, Festif Rudolf; Mola, Polce Yulian; Johannis, Dorkas Anomi (Journal of Language, Education, Literature, and Culture, 2025)
This bibliometric study explores the trends and patterns in writing assessment research conducted in Indonesia between 2013 and 2024. Employing a systematic approach, data were collected from Scopus and Google Scholar databases using targeted keywords related to writing assessment and the Indonesian EFL context. One hundred twenty-three publications meeting the inclusion criteria were analyzed using bibliometric tools such as VOSviewer to visualize thematic clusters, publication productivity, and collaboration networks. The findings reveal a steady increase in research output, especially after introducing major educational reforms like Kurikulum 2013 and Merdeka Belajar. Key thematic areas identified include formative assessment practices, integrating technology and AI-based writing feedback tools, rubric development aligned with national qualification frameworks, and assessing higher-order thinking skills. Collaboration analysis shows a growing network of researchers and institutions contributing to improving writing assessment knowledge in Indonesia. Despite these advances, gaps remain in methodological diversity, dissemination in local languages, and stronger links between research and classroom practice. The study highlights the need for enhanced professional development and policy support to foster effective, context-sensitive writing assessment practices. Limitations include potential exclusion of grey literature and the evolving nature of citation metrics. Recommendations for future research emphasize mixed-method approaches, expanded data sources, and closer researcher-practitioner collaboration. This study offers valuable insights for scholars, educators, and policymakers aiming to improve writing assessment frameworks and ultimately enhance students’ writing competence in Indonesian EFL settings.